التعايش المذهبي بين المالكية والحنابلة في مصر والشام خلال العصر المملوكي - رمضانى, فوزي (جامعة الوادي - University of Eloued, 2022)
يُعالج هذا المقال العلاقات بين المالكية والحنابلة في مصر والشام خلال العصر المملوكي، ويهدف أساسا إلى استجلاء مظاهر الانسجام والتعايش بينهما خلال تلك الفترة، والذي تجسّد في قنوات متنوعة ومتعددة، ما جعَلنا نستنتج ونُقرر أنّ ذلك هو المسْلك الأصيل في التعامل بين المذاهب السُّنِّية، والنموذج الراقي الذي ينبغي أن يُعمّم على بقية المذاهب، وبالتالي فإننا نوصي من يتطلع إلى البحث في تاريخ العلاقات بين المذاهب- خاصة السُّنِّية منها- أن يُبيِّن الوجه المُشرق لها ولا ينساق وراء دعاة التهويل والتشويه، فيقع في فخ التعصب المذهبي المفضي إلى الفُرقة والشتات بين المسلمين ونحن في أمس الحاجة إلى رأب الصدع وجمع الكلمة . This article deals with the relations between the Malikis and the Hanbalis in Egypt and the Levant during the Mamluk era, and it mainly aims to clarify the manifestations of harmony and coexistence between them during that period, which was embodied in various and multiple channels, which made us conclude and decide that this is the original course in dealing between Sunni sects, and therefore we recommend that anyone looking to research the history of relations between sects - especially the Sunni ones - to show the bright side of them and not be tempted by advocates of intimidation and distortion, so they fall into the trap of sectarian fanaticism that leads to division and diaspora among Muslims.
مقال
Keywords: مِصر، بلاد الشام، العصر المملوكي، التعايش المذهبي، المذهب المالكي، المذهب الحنبلي; Egypt, the Levant, the Mamluk era, sectarian coexistence, the Maliki school of thought, the Hanbali school of though